Residual strength prediction based on size effect of cracked concrete members - Ince, Ragip; Fenerli, Cenk (Emerald Group Publishing Ltd, 2022)
In engineering materials, defects, such as cracks, may occur during production and/or owing to various reasons. One of the aims of fracture mechanics is to determine the fracture toughness-based residual strength of structural members with cracks. A quasi-brittle material, such as concrete or rock, may include certain defects, such as voids and cracks, even before being exposed to loads. Experimental analyses on concrete members indicated that specimens' nominal strength values decreased as their sizes increased while specimen geometry remained the same. In fracture mechanics, this condition is defined as the 'size effect' in both concrete and reinforced concrete units. In the literature, numerous theoretical and experimental studies have been conducted on beams, while compact split-tension specimens, particularly notched ones, are limited. In this study, six series of notched beams with three different sizes and notched square prismatic specimens with four different sizes were tested. According to the test results, the peak loads were analysed by using the fundamental theorem of the modified size effect law. In conclusion, two formulae were proposed to predict the flexural strength and the splitting strength of quasi-brittle bodies with cracks.
Keywords: cracks and cracking; structural design; testing; structural elements